2012
DOI: 10.1038/ijo.2012.193
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of body mass index and body composition in atomic bomb survivors

Abstract: This is the first study to report a significant dose response for BMI and body composition 50 years after A-bomb radiation exposure. We will need to conduct further studies to evaluate whether these alterations affect health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
2
7
1
Order By: Relevance
“…has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15). Moreover, emerging evidence from mouse studies suggests direct interactions between diet-induced obesity and biological responses to radiation, e.g., DNA double-strand breaks, microRNA expression and cell survival (16,17).…”
Section: Introductionsupporting
confidence: 51%
“…has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15). Moreover, emerging evidence from mouse studies suggests direct interactions between diet-induced obesity and biological responses to radiation, e.g., DNA double-strand breaks, microRNA expression and cell survival (16,17).…”
Section: Introductionsupporting
confidence: 51%
“…However, gender differences in the plasma metabolome have been reported (Trabado et al 2017). Gender differences in radiation damage and radiation-induced metabolic diseases have also been suggested but remain poorly defined (Tonorezos et al 2012;Tatsukawa et al 2013;Zhang et al 2014). Additionally, gender differences in the field of radiobiology, including ARS as well as the delayed effects of acute radiation exposure (DEARE) remain under-studied.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information regarding high-level radiation exposure-induced cachexia or muscle wasting. Studies on atomic bomb survivors 50 years after the event showed that atomic bomb radiation was associated significantly and negatively with body mass index and appendicular lean mass, even though the estimated radiation exposures were less than 4 Gy 29 . In the Chernobyl nuclear accident, patients presented with the typical hematological, cutaneous, gastrointestinal syndromes, and neurological/psychological disorders.…”
Section: Discussionmentioning
confidence: 99%